The Effect of Islamic Service Quality on Customer Satisfaction and Loyalty in Islamic Banks in Indonesia - Anjelisa, Anjelisa; Fatmawati, Indah; Nuryakin, Nuryakin (International Journal of Management Science and Information Technology, 2023)
The performance of Islamic banking in Indonesia continues to improve year after year, but the market share of conventional banking that continues to dominate demonstrates that the existence of Islamic banking in Indonesia's dual banking system is still in the shadow of conventional banking. The goal of this research is to look at how customer perceptions of Islamic service quality affect customer satisfaction and loyalty to Islamic banks in Indonesia. Structural Equation Modeling (SEM) with AMOS as an analysis tool is used in data analysis procedures. According to the study's findings, the quality of Islamic services has a positive and significant influence on customer happiness and loyalty, and customer satisfaction has a positive and significant influence on customer loyalty. These findings highlight the need for evaluating service quality in the context of Islamic banks. If the compliance dimension is thoroughly implemented in the operation of the Islamic banking firm, Islamic banking can have a competitive advantage over conventional banking.